CAUSES OF DAMAGE TO COTTON IN THE PNEUMATIC TRANSPORT SYSTEM AND WAYS TO REDUCE IT - Lazizbek, Saidmuradov Mirzohid (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the occurrence of seed damage during the transportation of raw cotton to the production shops and the occurrence of defects that affect the quality of fiber on these indicators, and conducted research to reduce the increase in fiber defects.